Development of energy harvesting from burning process for community need via IoT based system - Rahaini Mohd Said; Nagen Krishnan; Amardeep Singh Dhillon; Nor Hafizah Hussin; Shamsul Fakhar Abd Gani (Institute of Advanced Engineering and Science, 2020)
In this paper, a proposal was made to recreate an energy harvesting technique using biomass energy such as twigs, leaves, wood, paper, and charcoal emitted by burning the said materials and harvest the energy from the released heat. The harvested energy is then converted into a voltage that can be used to charge devices such as mobile phones or even turn on emergency lights. In terms of its application, the system can be used to provide backup power during disaster especially during a flood or other causes of power outages. The system can also be used to charge electronic devices during outdoor activities in remote areas where electricity is inaccessible such as camping or other outdoor activities. This system can produce free electric power that can also be extremely beneficial in third world countries. The cost of the module used is also much cheaper than other existing harvesting methods such as solar panels or water turbines. Based on test data collected using IoT platform, charcoal was determined as the best material in terms of output power generated.